2019
DOI: 10.1080/17429145.2019.1629035
|View full text |Cite
|
Sign up to set email alerts
|

Volatile profiles of three tree species in the northeastern China and associated effects onSirex noctilioactivity

Abstract: The wood-boring wasp, Sirex noctilio, is an invasive pest of numerous species of pine trees worldwide. The female S. noctilio wasps selectively lay eggs on different pine trees. The relationship between host volatile organic compounds and the wood wasps remains elusive. Here, the behaviors of the wood towards the host volatiles wasps were investigated. In Junde Forest Farm, three tree species, Pinus sylvestris var. mongolica, Larix gmelinii (Rupr.) Kuzen., and P. koraiensis Sieb.et Zucc., were girdled. Four tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…2022), Larix olgensis (Chen et al 2013), Pinus koraiensis (Liu et al 2021), Pinus tabuliformis(Wang et al 2006) and so on. Previously, α-pinene and limonene were identi ed in the volatiles of L. gmelinii and S. oblata(Qiang et al 2019, Ju et al 2021, consistent with our results. The volatiles of S. oblata leaves were extracted by hydrodistillation, and found to contain α-pinene, which varied greatly with different seasons(Hui et al 2008), but the content and proportion of compounds were discrepant with those in our experiment.…”
supporting
confidence: 92%
“…2022), Larix olgensis (Chen et al 2013), Pinus koraiensis (Liu et al 2021), Pinus tabuliformis(Wang et al 2006) and so on. Previously, α-pinene and limonene were identi ed in the volatiles of L. gmelinii and S. oblata(Qiang et al 2019, Ju et al 2021, consistent with our results. The volatiles of S. oblata leaves were extracted by hydrodistillation, and found to contain α-pinene, which varied greatly with different seasons(Hui et al 2008), but the content and proportion of compounds were discrepant with those in our experiment.…”
supporting
confidence: 92%
“…Besides α-pinene, volatile organic compounds (VOCs) from P. tabuliformis also includes limonene, β-pinene, and α-caryophyllene [ 61 ]. Xu et al [ 62 ] found that the VOCs from P. koraiensis included α-pinene, β-pinene, and sabinene. Insects can successfully survive on their host plants by producing detoxifying enzymes, e.g., P450s, UGTs, and CEs [ 25 , 30 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, fieldwork has indicated that the only infested conifer species in China to date is P. sylvestris var. mongolica, even when other potential hosts are present in the same forest [37]. As is characteristic of invasive pests, S. noctilio appears to be harmless in the natural distribution area of its favorite host tree species.…”
Section: Host Unity Of S Noctilio In Chinamentioning
confidence: 99%